Relatório de estágio técnico profissional em medicina veterinária: clínica cirúrgica de pequenos animais - Strauss, Gabrieli (2023)
The Professional Technical Internship (ETP) refers to the stage of graduation where the student has the opportunity to put into practice and improve all their theoretical knowledge acquired during the course break in Veterinary Medicine, leading them to the intended area of ​​activity. professionally. The ETP was practiced in the clinical-surgical area of ​​small animals, under the academic guidance of Veterinary Doctor Prof. Dr. Renato do Nascimento Libardoni, at the Veterinary Hospital of the University of Passo Fundo (HV-UPF), from August 2nd to November 3rd, 2023, totaling 510 hours (Appendix A). Through ETP, I had the opportunity to immerse myself in the dynamics of a teaching hospital, more specifically in the clinical-surgical sector. Furthermore, during this interval, I was able to actively participate in surgical procedures in the operating room, collect biological material, provide assistance in outpatient and emergency procedures, in addition to contributing to the execution of imaging exams. Therefore, this report aims to describe the internship environment, the general activities carried out, and the specific activities that I had the opportunity to follow in the small animal clinical-surgical sector. This information was organized by body systems and affected species, with the aim of providing a clearer understanding to the reader. Furthermore, at the end of this report, I present a case report of a canine presenting a foreign body (FB) in the esophagus region, which was initially submitted to an endoscopy. However, as it was not possible to resolve the case, a new intervention had to be carried out, in which she consented to access via thoracotomy, followed by esophagotomy to remove the FB. After the end of the procedure, another surgical intervention was necessary through exploratory celiotomy for gastrostomy, due to the lesions found in the esophagus. In conclusion, the ETP was a fundamental experience for personal and professional growth, which gave me the opportunity to experience the daily life of a veterinarian, improve my clinical-surgical reasoning skills and learn to deal with the challenges faced daily.